Al-Istifâdah min Al-Al'âb Al-Lughawiyah li Ta'lîm Al-Lughah Al-'Arabiyyah li Al-Sâsâkiyyîn Al-Mubtadi-în bi Istikhdâm Al-Kalimât Al-Sâsâkiyyah Dzat Ashl 'Arabiy fî Qômus Al-Lughah Al-Sâsâkiyyah (Nazir Toir) - Ardiansyah; kosim, Nanang (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2023)
تهدف هذه الدراسة إلى اكتشاف الكلمات الساساكية ذات أصل عربي في قاموس اللغة الساساكية (nazir toir) وهذا المبدأ ينبني على أن بين اللغتين الساساكية و العربية وهي لغة القرآن الكريم علاقة وتيدة منذ دخول الإسلام في جزيرة لومبوك. وتهدف هذه الدراسة إلى كيفية تصميم ألعاب لغوية لتعليم اللغة العربية للساساكيين المبتدئين باستخدام الكلمات الساساكية ذات أصل عربي.و اعتمدت هذه الدراسة على المنهج الوصفي التحليلي الذي يصف وصفا دقيقا لموضوع الدراسة وذلك من خلال تحليل الكلمات الساساكية ذات أصل عربي بالعتماد على القاموس الساساكي والعربي، وتصميمها في الألعاب اللغوية.وأثبتت هذه الدراسة إمكانية الاستفادة من الكلمات الساساكية ذات أصل عربي في تعليم اللغة العربية للومبوكيين من خلال تصميم ألعاب لغوية. This study aimed to express an absorption words of Sasak language derived from Arabic language in the Nazir book. This principle is based on the fact that between Sasak language and Arabic, language of the qur'an, which has a reltionship and affiliation since the introduction of Islam in Lombok island. This study also aimed how to design a language game to teach Arabic language for the beginners from Sasak tribes by using Sasak words derived from Arabic. This study used descriptive analytic approach, which described an accurate description about the subject of the research. Through analysis the words of Sasak language derived from Arabic, based on Sasak and Arabic dictionary and there are sentences designed into language game. This study showed the exsistence of Sasak words derived from Arabic in Sasak dictionary (Nazir book) from the letter A-R as an example and the total reaches one hundred and fourty five words. This study concluded that there is a change of Arabic words that entered to Sasak Language and the sentences divided into four classes